Telemedicine practice guidelines of India, 2020: Implications and challenges - Dinakaran, Damodharan (Indian J Psychiatry, 2021)
Telemedicine Guidelines of India, 2020 promises to pave a road map for regularization and diversification of teleconsultation services across the country. This guideline is the need of the hour, especially during the current coronavirus disease pandemic. All modes of communications (text, audio, video, etc.) between the service provider and user are included in the broad rubric of the guidelines. Scope, inclusions, exclusions, and restrictions are clearly specified in the guideline. Medications are grouped and listed for the specific type of consultation, and restricted drugs are notified. This guideline especially helps mitigate the gaps in legislation and reduces the uncertainty while providing a practical, safe, and cost-effective framework to improve healthcare service delivery in this article; the authors discuss the implications of this new guideline and the challenges during the implementation of teleconsultation services across the country.